Post-entrapment modification of residual inclusion pressure and its implications for Raman elastic thermobarometry - Zhong, Xin; Moulas, Evangelos; Tajcmanová, Lucie (Solid earth, 2020)
Residual pressure can be preserved in mineral inclusions, e.g. quartz-in-garnet, after exhumation due to differential expansion between inclusion and host crystals. Raman spectroscopy has been applied to infer the residual pressure and provides information on the entrapment temperature and pressure conditions. However, the amount of residual pressure relaxation cannot be directly measured. An underestimation or overestimation of residual pressure may lead to significant errors between calculated and actual entrapment pressure. This study focuses on three mechanisms responsible for the residual pressure modification: (1) viscous creep; (2) plastic yield; (3) proximity of inclusion to the thin-section surface. Criteria are provided to quantify how much of the expected residual pressure is modified due to these three mechanisms. An analytical solution is introduced to demonstrate the effect of inclusion depth on the residual pressure field when the inclusion is close to the thin-section surface. It is shown that for a quartz-in-garnet system, the distance between the thin-section surface and inclusion centre needs to be at least 3 times the inclusion radius to avoid pressure release. In terms of viscous creep, representative case studies on a quartz-in-garnet system show that viscous relaxation may occur from temperatures as low as 600-700 ∘C depending on the particular pressure-temperature (P-T) path and various garnet compositions. For quartz entrapped along the prograde P-T path and subject to viscous relaxation at peak T above 600-700 ∘C, its residual pressure after exhumation may be higher than predicted from its true entrapment conditions. Moreover, such a viscous resetting effect may introduce apparent overstepping of garnet nucleation that is not related to reaction affinity.
Gesehen am 26.03.2020